1288 IMPROVING STAFF AWARENESS OF FRAILTY IN THE EMERGENCY DEPARTMENT: A MULTI-DISCIPLINARY QUALITY IMPROVEMENT PROJECT. (16th January 2023) - May, G P; Bennett, L A; Loughrey, J P; Littlewood, N; Mitchell, L
Abstract: Introduction: Comprehensive Geriatric Assessment (CGA) improves outcomes for frail older adults in acute hospitals. Patients aged 75 and over admitted into the Emergency Department (ED) at the QEUH will automatically generate a "frailty icon" on their electronic record. The number of frail people accessing emergency care is increasing. This Healthcare Improvement Scotland (HIS) frailty tool prompts staff to assess for frailty and refer to the local Frailty Pathway if appropriate. We designed a multidisciplinary quality improvement project (QIP) to increase completion of the frailty icon and the number of referrals to the frailty service from the ED. Methods: Both medical and nursing staff in the ED were targeted for intervention. Weekly data was collected on the percentage of patients aged 75 and above who were discharged from the ED with a "frailty icon" completed over a 3-month period. Our main intervention was to hold a frailty awareness month. This involved multiple sub-interventions such as; announcements at handovers, e-mails, word-of-mouth, and posters. Results: The weekly percentage of completed "frailty icons" increased from 28% 2 weeks pre-intervention (n = 283) to 48% in 1 month (n = 258). A peak of 57% (n = 293) completed icons was achieved immediately after our intervention. These increases were then sustained for a further 6 weeks with a weekly average baseline of 45.2% completion (average n = 281). Increased "frailty icon" completion in the ED led to a 100% increase in referrals to the frailty pathway. Conclusion: Increasing awareness of frailty amongst ED staff results in increased front door assessment for frailty, and subsequent referral to the frailty team. This allows for more patients to receive a CGA. Multidisciplinary QIPs utilise the skills of diverse staff groups to best achieve sustainable change.